Emotional appeals effectiveness in enhancing charity digital advertisements. Issue 4 (31st July 2022) - Yousef, Murooj; Dietrich, Timo; Rundle‐Thiele, Sharyn; Alhabash, Saleem
Abstract: Advertising appeals effectiveness has long been a point of debate in the literature. This study empirically tests hope and shame online advertisements aimed at enhancing donation quality to charities. Following a sequential research design the current research carries two studies to tests the effect of hope and shame appeal messages on social media on behavioral engagement measures, guided by the multi‐actor engagement framework. Findings indicate shame appeals framed as losses are more effective in driving engagement than hope gain framed messages. The overall findings provide supporting evidence for the interplay between negative emotions and message framing. To achieve higher engagement and trigger behavior change while utilizing budgets effectively, charities would benefit from utilizing loss framed and shame inducing advertising messages.